Attention and Conscious Perception in the Hypothesis Testing Brain - Hohwy, Jakob (Frontiers in Psychology, 2012)
Conscious perception and attention are difficult to study, partly because their relation to each other is not fully understood. Rather than conceiving and studying them in isolation form each other it may be useful to locate them in an independently motivated, general framework, from which a principled account of how they relate can then transpire. Accordingly, these mental phenomena are here reviewed through the prism of the increasingly influential predictive coding framework. On this framework, conscious perception can be seen as the upshot of prediction error minimisation and attention as the optimisation of precision expectations during such perceptual inference. This approach maps on well to a range of standard characteristics of conscious perception and attention, and can be used to explain a range of empirical findings on their relation to each other.